2013
DOI: 10.1016/j.jcrc.2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Behavior observation of major noise sources in critical care wards

Abstract: PurposeTo investigate the behaviour patterns of typical noise sources in critical care wards, and relate their patterns to healthcare environment in which the sources adapt themselves in several different forms. Methods An effective observation approach was designed for noise behaviour in the critical care environment. Five descriptors have been identified for the behaviour observations, namely interval, frequency, duration, perceived loudness and location. Both the single-bed and multiple-bed wards at the sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 15 publications
(13 reference statements)
1
22
0
1
Order By: Relevance
“…Thus, a quieter environment should be ensured especially at night in ICUs, in accordance with the recommendations of the WHO and the EPA. Noise levels are especially high in ICUs that have multiple patient beds, because staff conversations and monitor alarms in nurses' stations and treatment areas and during nursing interventions cause excessive noise (Xie et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a quieter environment should be ensured especially at night in ICUs, in accordance with the recommendations of the WHO and the EPA. Noise levels are especially high in ICUs that have multiple patient beds, because staff conversations and monitor alarms in nurses' stations and treatment areas and during nursing interventions cause excessive noise (Xie et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to housing staff members from various professions (doctor, nurse, or auxiliary staff members), nurses’ stations are areas where medical notes, orders, and patient treatment cards are written, and where televisions and radios are often found (Oliveira et al., , p. 435). In ICUs where multiple patients are hospitalized, nurses’ stations cause a substantial amount of noise due to the daily chatter of the healthcare staff and the care‐related conversations of the nurses, doctors, and auxiliary staff related to care activities (Lawson et al., ; Oliveira et al., ; Xie, Kang, & Mills, ). A previous study showed that staff in multiple‐patient units spoke louder and held longer conversations than in single‐patient units (Xie et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In ICUs where multiple patients are hospitalized, nurses’ stations cause a substantial amount of noise due to the daily chatter of the healthcare staff and the care‐related conversations of the nurses, doctors, and auxiliary staff related to care activities (Lawson et al., ; Oliveira et al., ; Xie, Kang, & Mills, ). A previous study showed that staff in multiple‐patient units spoke louder and held longer conversations than in single‐patient units (Xie et al., ). Bailey and Timmons () showed that the noise level in a PICU increased in direct proportion to the number of staff members and devices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, some part of noise effects is associated with its impact on the nervous system and mental and behavioral status [15][16][17]. Li et al (2002) developed a road traffic noise prediction model based on local environmental standards, vehicle types and conditions of traffic [18].…”
mentioning
confidence: 99%